IgG3 donor–specific antibodies with a proinflammatory glycosylation profile may be associated with the risk of antibody‐mediated rejection after kidney transplantation. Issue 3 (18th December 2021) - Pernin, Vincent; Bec, Nicole; Beyze, Anaïs; Bourgeois, Alexis; Szwarc, Ilan; Champion, Coralie; Chauvin, Anthony; Rene, Céline; Mourad, Georges; Merville, Pierre; Visentin, Jonathan; Perrochia, Helene; et al.
Abstract : The pathogenicity of de novo donor‐specific antibodies ( dn DSA) varies according to their characteristics. While their MFI, complement‐fixing ability, and IgG3 subclass are associated with ABMR occurrence and graft loss, they are not fully predictive of outcomes. We investigated the role of the Fc glycosylation of IgG3 dn DSA in ABMR occurrence using mass spectrometry after isolation by single HLA antigen beads. Between 2014 and 2018, we enrolled 54 patients who developed dn DSA (ABMR− n  = 24; ABMR+ n  = 30) in two French transplant centers. Fucosylation, galactosylation, GlcNAc bisection, and sialylation of IgG3 dn DSA were compared between ABMR+ and ABMR− patients. IgG3 dn DSA from ABMR+ patients exhibited significantly lower sialylation (7.5% vs. 10.5%, p  < .001) and higher GlcNAc bisection (20.6% vs. 17.4%, p  = .008). Fucosylation and galactosylation were similar in both groups. DSA glycosylation was not correlated with DSA MFI. In a multivariate analysis, low IgG3 sialylation, high IgG3%, time from transplantation to kidney biopsy, and tacrolimus‐free regimen were independent predictive factors of ABMR. We conclude that a proinflammatory glycosylation profile of IgG3 dn DSA is associated with a risk of ABMR occurrence. Further studies are needed to confirm the clinical interest of DSA glycosylation and to clarify its role in determining the risk of ABMR and graft survival. Abstract : In a cohort of kidney recipients presenting de novo DSA, the authors show that a proinflammatory glycosylation profile of IgG3 DSA is associated with the risk of antibody‐mediated rejection.